PROBLEMS OF MAINTAINING SPIRITUAL SECURITY IN THE CONTEXT OF GLOBALIZATION - Rakhmankulov Farhod Rakhimkulovich (Western European Studies, 2025)
This article attempts to shed light on ideas and considerations such as the processes of globalization, the origin of its importance today, the concept of spiritual security, its meaning and essence, measures to maintain spiritual security in glaballshuv conditions.
Keywords: globalization; spirituality; spiritual security